SURGICAL CORRECTION OF CORNEAL DERMOID USING SUPERFICIAL KERATECTOMY AND THIRD EYELID FLAP IN A ROTTWEILER DOG - N. Krishnaveni; E. Kalaiselvan; A.R. Ninu; M. Madeena Begum (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 7 months old female Rottweiler dog was presented with the history of ocular discharge from the right eye and partially opening of the eyelid since 2 weeks from adoption. Ophthalmic examination revealed epiphora, blepharospasm, congested sclera, cloudy cornea with tissue like growth along with hairs on the lateral temporal limbal region on the right eye and the left eye had no abnormalities. Schirmer tear test and fluorescein dye test was performed. Based on the ophthalmic examination findings, the condition was diagnosed as corneal dermoid. Surgical excision of corneal dermoid was done to correct the abnormalities and animal had an uneventful recovery.